Studi Kasus Penerimaan Diri Transeksual Di Pondok Pesantren Waria Al-Fatah Yogyakarta - Rio Wahyu Nugroho; Indra Wahyudi; Fx Wahyu Widiantoro (LPPM Universitas Proklamasi 45, 2023)
ABSTRACT Transsexuals are individuals who feel that they are born with the wrong biological sex and consider themselves to be a group of the opposite sex. The background factors are internal (natural) and external (family and environmental influences). This study aims as a case study to find out what causes self-acceptance of transsexuals at the Pondok Pesantren Waria Al-Fatah Yogyakarta. The research method used is qualitative research using observation, interviews and documentation as data collection methods. This study used 2 (two) subjects including students from the Pondok Pesantren Waria Al-Fatah Yogyakarta. Based on the results of interviews and observations, it can be concluded that transsexual self-acceptance can be influenced by social support such as support from the community where they live, support from friends and most importantly family support